Sexual, preventive and social trajectories in unexpected pregnancies in youth segments in Chile - Palma, Irma (Última Década, 2020)
The article investigates unexpected pregnancies in juvenile segments within the Chilean society. It is oriented to understand its magnitude and social configuration, to include/understand its relation with the head-end process in the active sexuality and structuring of the sexual and preventive trajectories; and to explore the way in which this is used to express specific configurations of the social relations of generic and social stratification. Use of the Fifth National Survey of Youth, made possible by the National Institute of Youth in 2006.